PERSEPSI MASYARAKAT DI KECAMATAN ANGKOLA BARAT TERHADAP PEMBAGIAN HARTA WARISAN BAGI ANAK PEREMPUAN DALAM ADAT TAPANULI SELATAN (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2017)
The problem in this study is how the implementation of the distribution of inheritance for girls and what are the causal factors of girls do not get a share of inheritance in the Angkola Barat sub-district in terms of applicable customary law. Based on the results of the above research, the results show that the distribution of inheritance for girls in the Angkola Barat sub-district according to customary law from the results of interviews and questionnaires to the community of Angkola Barat sub-district can be assessed that Angkola Barat Subdistrict has not implemented the distribution of inheritance for girls according to Islamic law, but still uses customary law. So with this the Angkola Barat community still uses customary law in terms of the distribution of inheritance and still excludes Islamic law because it is a hereditary habit. The law used in completing the inheritance is only still using customary law. This is due to the strong influence of culture and customs and the lack of public understanding of Islamic law.